Hydrothermal synthesis of I-doped Bi2WO6for using as a visible-light-driven photocatalyst - Anukorn Phuruangrat (2018)
© 2018 Elsevier B.V. Bi2WO6and I-doped Bi2WO6photocatalysts were hydrothermally synthesized at 180 °C for 24 h. The as-synthesized products were characterized by X-ray diffraction (XRD), UV–visible spectroscopy, transmission electron microscopy (TEM), selected area electron diffraction (SAED) and X-ray photoelectron spectroscopy (XPS). The analytical results showed that Bi2WO6and I-doped Bi2WO6photocatalysts are Aurivillius orthorhombic phase, certifying that I atoms were incorporated in the Bi2WO6matrix. The photocatalytic activities of the as-synthesized Bi2WO6and I-doped Bi2WO6samples were evaluated via photodegradation of rhodamine B induced by visible radiation. In this research, the I-doped Bi2WO6photocatalyst has higher photocatalytic activity than pure Bi2WO6.